2018
DOI: 10.1016/j.clcc.2018.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Neoadjuvant Therapy and Rectal Surgery on Health-related Quality of Life in Patients With Rectal Cancer During the First 2 Years After Diagnosis

Abstract: Rectal cancer treatment is associated with a significant decline in QOL during the first 6 months after the diagnosis. Within 2 years, most patients return toward pretreatment functioning but could still experience poorer functioning and treatment-related symptoms compared with the general population. These findings support shared decision-making and emphasize the need for postoperative supportive care and novel treatment approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
58
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 51 publications
0
58
1
Order By: Relevance
“…There are several reasons why patients may refuse recommended rectal cancer surgery. These include avoidance of radical surgery and quality of life concerns, 14,20 personal values, 15,16 communication difficulties with providers, 18,19 and the racial/socioeconomic barriers discussed previously 12,17,18 . Patients are often concerned with quality of life following rectal cancer surgery given the high rate of morbidity following surgery, including low anterior resection syndrome, sexual dysfunction, and permanent colostomy.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…There are several reasons why patients may refuse recommended rectal cancer surgery. These include avoidance of radical surgery and quality of life concerns, 14,20 personal values, 15,16 communication difficulties with providers, 18,19 and the racial/socioeconomic barriers discussed previously 12,17,18 . Patients are often concerned with quality of life following rectal cancer surgery given the high rate of morbidity following surgery, including low anterior resection syndrome, sexual dysfunction, and permanent colostomy.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, in a survey, patients said they were willing to accept higher rates of tumor recurrence and decreased survival to avoid radical surgery 15 . Several studies have indeed shown that there is a decrease in quality of life after surgery for rectal cancer, although this decrease often returns to baseline within 6 months to 2 years after surgery 20,30 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations